Synthesis, Characterization and Printing Application of Solvent Dyes Based on 2-Hydroxy-4-n-octyloxybenzophenone - Bharat C. Dixit; Hitendra M. Patel (E-Journal of Chemistry)
Solvent dyes have been prepared by the coupling of diazo solution of different aromatic amines with 2-hydroxy-4-n-octyloxybenzophenone. The resultant dyes were characterized by elemental analysis as well as IR and 1H NMR spectral studies. The UV-Visible spectral data have also been discussed in terms of structure property relationship. The printing of all the dyes on cotton fiber was monitored. The result shows that better hue was obtained on printing on cotton fiber and it is resulted in yellow to reddish brown colorations which showed a good fastness to light, with poor to good fastness to washing, perspiration and sublimation, however it shows poor rubbing fastness.